System Analysis of Dengue Virus Surveillance in BBTKL PP Surabaya Year 2012–2014 - Atina Husnayain; Kurnia Dwi Artanti; Acub Zaenal (Jurnal Berkala Epidemiologi, 2015)
Changes in the distribution of dengue virus serotypes have occurred in Indonesia. These changes must be monitored continuously through laboratory-based epidemiological surveillance of dengue viruses, one of which is carried out by the Center of Environmental Health and Disease Control Agency (BBTKLPP) Surabaya. The purpose of this study is to determine the workflow, identify problems, determine priority problems, find the cause of the problem, and provide alternative solutions related to problems in the implementation of molecular epidemiological surveillance of dengue viruses that have been carried out by BBTKLPP Surabaya. This research is a descriptive study with informants is molecular epidemiological surveillance officers of the dengue virus in BBTKLPP Surabaya. Data processing and analysis are done descriptively and presented in narrative form. The results showed that the molecular epidemiological surveillance workflow of the dengue virus in BBTKLPP Surabaya consisted of collecting blood specimens from patients and vectors, vector surveys and supporting data collection, rapid diagnostic test examinations, and polymerase chain reaction, data processing and analysis and information dissemination. The main problem in implementing this surveillance is the quality of the information generated is still low. The problem tree analysis results show that the cause of the problem that can be intervened is incomplete supporting data and data not collected in one storage medium. An alternative solution to overcome this problem is through the use of a database management system is Epi-info.